2020
DOI: 10.1016/j.ijpam.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and iron profile among children and adolescent with low socio-economic status

Abstract: Background: A national health survey in Indonesia conducted in 2013 showed that the prevalence of anemia in school-aged children and adolescents tripled from a survey conducted in 2007. Children and adolescents are particularly susceptible to iron deficiency anemia (IDA) and iron deficiency (ID) because of their rapid growth and puberty. Teenage girls are at risk because of their menstrual bleeding. Low socioeconomic status in children and adolescents is also a strong risk factor for experiencing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 16 publications
4
31
4
6
Order By: Relevance
“…The present finding is higher than study report from Tigray, Ethiopia 7.1% [12], prevalence of Anaemia was 14% [22]. On other side, the current finding is lower than study report of Maharashtra, India 87% [23], rural adolescent 75% [24]; in Bangladesh 51.6% [25]; in Tertiary Care Hospital 50% [26]; Jimma, South West Ethiopia 37.6% [27]; South west of Ethiopia 28% [6]; and Afar, North East Ethiopia 22.8% [29].…”
Section: Discussioncontrasting
confidence: 84%
“…The present finding is higher than study report from Tigray, Ethiopia 7.1% [12], prevalence of Anaemia was 14% [22]. On other side, the current finding is lower than study report of Maharashtra, India 87% [23], rural adolescent 75% [24]; in Bangladesh 51.6% [25]; in Tertiary Care Hospital 50% [26]; Jimma, South West Ethiopia 37.6% [27]; South west of Ethiopia 28% [6]; and Afar, North East Ethiopia 22.8% [29].…”
Section: Discussioncontrasting
confidence: 84%
“…Low socioeconomic status has been known to be a risk factor of IDA . However, we found that our prevalence of IDA is 18 (60.0) suffering from low scale of S.E.S this study accepted with Andriastuti M. 9 The overall prevalence of IDA in them study was 14.0 . Knowledge: Show in our results knowledge answers near half study sample with their children previously diagnose with IDA was 16 (53) this results accepted with Al-jamri A.…”
Section: Discussionsupporting
confidence: 45%
“…Whereas in study conducted by Andriastuti et al, the median age of the subjects was found to be 11 years and subjects belonging to age group of 10-18 years had highest prevalence of iron deficiency. 20 The BMI of the students was determined using their height and weight. The prevalence of underweight, overweight and obesity was 61 (14.77%), 53 (12.83%) and 2 (0.48%) respectively.…”
Section: Discussionmentioning
confidence: 99%